PENGARUH PENDIDIKAN KESEHATAN TENTANG MENCUCI TANGAN TERHADAP PENGETAHUAN DI MASA COVID 19 PADA ANAK SEKOLAH - Elsi Rahmadani; Marlin Sutrisna (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Every year, 3.5 million children die from diarrheal diseases and ARI and Covid 19 which can be minimized by washing hands. The purpose of this study was to determine the effect of health education on hand washing on knowledge of students at MIN 2 Bengkulu City. The method used is a method with a pre and post one group Quasi Experiment approach. The sample in this study amounted to 23 respondents using total sampling technique. This study uses SPSS with the Wilcoxon test bivariate statistical test with a value of = <0.05. The results of the univariate analysis showed that the average knowledge value before was 5.30 and the average knowledge value after health education on washing hands was 12.87. The results of the bivariate analysis showed that there was an effect of health education on hand washing on students' knowledge (p value = 0.000). Researchers suggest that schools can routinely provide learning about health, especially about washing hands for elementary school children.